An empirical analysis of bank specific factors affecting interest rate of Ugandan banking financial institutions - Tumwine, Sulait; Sejjaaka, Samuel; Bbaale, Edward; Kamukama, Nixon (World Journal of Entrepreneurship, Management and Sustainable Development, 2018)
Purpose: The purpose of this paper is to investigate the effect of bank specific factors on interest rate in banking financial institutions (BFIs) of Uganda. Design/methodology/approach: To analyze the effect, an OLS random effects regression estimate on a data set of 24 banks from 2008 to 2016 from Bank of Uganda Depository Corporation survey was carried out. Studied bank specific factors including liquidity, operational efficiency, credit risk, capitalization and lending ratio are considered. Findings: The results indicate that liquidity, operational efficiency, capitalization and lending out ratio affect the interest rate while credit risk does not. Research limitations/implications: The study has confirmed that bank specific factors influence interest rate and other factors such as industry-level and indirect macroeconomic indicators need to be explored. The differences in categories of banks on interest rate would be of importance. Finally, this study concentrated on banks in Uganda, future study would focus on the comparison of Ugandan banks with those of other countries in the East African Region. Practical implications: Bank managers should invest in up-to-date technology to reduce operational costs and improve efficiency. Managers of bank should take interest on equity mobilization, because it constitutes a cheaper source of capital to finance asset used in operations and long-term needs of borrowers financing. Government should consider a legislation that provides incentives toward savings and reduction in tax for bank inputs. Originality/value: This is the first study that investigates the effect of bank specific factors on interest rate in Uganda’s BFIs.
Keywords: Interest rate; Bank specific factors; Banking financial institutions